Manipulating On/Off Single-Molecule Magnet Behavior in a Dy(III)-Based Photochromic Complex - Ma, Yu-Juan; Hu, Ji-Xiang; Han, Song-De; Pan, Jie; Li, Jin-Hua; Wang, Guo-Ming (Journal of the American Chemical Society, 2020)
Exploitation of room temperature (RT) photochromism and photomagnetism to induce single-molecule magnet (SMM) behavior has potential applications toward optical switches and magnetic memories, and remains a tremendous challenge in the development of new bulk magnets. Herein, a series of chain complexes [Ln (H-HEDP) (H -HEDP) ]·2H -TPT·H -HEDP·10H O ( ; Ln = Dy ( ), Gd ( ), and Y ( ); HEDP = hydroxyethylidene diphosphonate; TPT = 2,4,6-tri(4-pyridyl)-1,3,5-triazine) were synthesized by solvothermal reactions. All the compounds exhibited reversible photochromic and photomagnetic behaviors via UV light irradiation at RT, induced by the photogenerated radicals via a photoinduced electron transfer (PET) mechanism. More importantly, the PET process induced significant variations in magnetic interactions for the Dy(III) congener. Strong ferromagnetic coupling with remarkably slow magnetic relaxation without applied dc fields was observed between Dy ions and photogenerated O radicals, showing SMM behavior after RT illumination. For the first time, we observed the reversible RT photochromism and photomagnetism in the lanthanide-based materials. This work realized the radicals-actuated on/off SMM behavior via RT light irradiation, providing a new strategy for constructing the light-induced SMMs.